Sedentary behavior and motor competence in children and adolescents: a review - Santos, Guilherme dos; Guerra, Paulo Henrique; Milani, Suedem Andrade; Santos, Ariane Brito Diniz; Cattuzzo, Maria Teresa; Ré, Alessandro Hervaldo Nicolai (Revista de Saúde Pública, 2021)
OBJECTIVE: To synthesize evidence from studies that analyzed the associations between sedentary behavior and motor competence in children and adolescents. METHODS: Systematic review of original articles that analyzed possible associations between sedentary behavior and motor competence in children and adolescents (3–18 years of age), without restrictions on study design, instruments and analysis protocols. The articles were identified through searches in the PubMed, Web of Science, Academic Search Premier, Cinahl, Medline and SPORTDiscus databases, as well as in reference lists. The level of evidence was evaluated according to the amount of studies that reported statistical significance in the associations between the variables and the quality of the articles (risk of bias). RESULTS: Of 2,462 initial studies, 22 composed the synthesis (two interventions, nine longitudinal and eleven cross-sectional studies). Of these, in 13, we observed negative associations between the variables, more often in the age group of seven to fourteen years. In the analysis of risk of bias, the main limitations of the studies were “convenience sampling” and “no description of sample sizing”. CONCLUSIONS: The available evidence suggests that sedentary behavior is negatively associated with motor competence in elementary school children, although the evidence is uncertain in the preschool years; the synthesis of results from longitudinal studies suggests that sedentary behavior negatively affects the development of motor competence. It is important that future studies have greater control over sociocultural determinants and deepen knowledge regarding sex and age, as well as the methods and indicators used to evaluate the two variables.